# help with this math problem!?

### 4 Answers

- Φ² = Φ+1Lv 74 weeks ago
x³ + x² - x - ...

= x³ - 2x² + 3x² - 6x + 5x ...

= (x-2)x² + (x-2)3x + 5x ...

= (x-2)(x²+3x) + 5x ...

The only answer starting with x²+3x is D. If one answer is correct it must be this one.

- Log in to reply to the answers

- 4 weeks ago
(x - 2) * (ax^2 + bx + c + d/(x - 2)) = x^3 + x^2 - x - 10

ax^3 + bx^2 + cx - 2ax^2 - 2bx - 2c + d = x^3 + x^2 - x - 10

ax^3 + (b - 2a) * x^2 + (c - 2b) * x + (d - 2c) = x^3 + x^2 - x - 10

ax^3 = x^3

a = 1

(b - 2a) * x^2 = x^2

b - 2a = 1

b - 2 = 1

b = 3

(c - 2b) * x = -x

c - 2b = -1

c - 6 = -1

c = 5

d - 2c = -10

d - 10 = -10

d = 0

(x - 2) * (x^2 + 3x + 5)

- Log in to reply to the answers

- Iggy RockoLv 74 weeks ago
...............x^2 +3x + 5

......----------------------

x-2|x^3 + x^2 - x - 10

......x^3 - 2x^2

......-------------

..............3x^2- x

..............3x^2-6x

..............---------

......................5x - 10

......................5x - 10

......................---------

..............................0

- Log in to reply to the answers